Eudemonologia: a possibilidade de se viver menos infeliz no mundo segundo Arthur Schopenhauer - Silva Filho, Antonio Francisco da (2018)
The present dissertation is a theoretical-bibliographical research about eudemonology as the possibility of living less unhappy in the world according to the thinking of the voluntarist philosopher Arthur Schopenhauer. In order to explain how it is possible to find in the philosopher father of pessimism the possibility of living in a world that ontologically is Will. It is the axis of Schopenhauer's philosophy. For the thinker, the Will is in everything and manifests itself in everything, presents itself phenomenally in the most varied degrees. It is the noumenon, the thing-in-itself mentioned in Kant's philosophy. Thus this world may be considered the worst of all possible worlds, not being born as the greatest of all sorts, and this world is likened to true hell. It must be realized that if existence is attached to what we understand as Will, this is itself chaotic, the possibility of and eudemonology is rejected by the deterministic ontology itself that conceives of all in a condition of eternal dissatisfaction, reason why the world would be nothing more than a oscillation between pain and boredom. The eudemonology will be euphemistic expression, because in the philosophical structure presented by Schopenhauer it is impossible to be happy. Nevertheless, the philosopher already at the end of his life, elaborated the Parerga and Paralipomena, to which belong the Aforismas of Wisdom of Life. These, together with The Art of Being Happy, contain advice for a less unhappy life, in keeping with the whole conjuncture of his philosophical "organism." In this context, we will try to demonstrate that there is no discrepancy in these two spheres of Schopenhauer's philosophy, but that, on the contrary, we can treat them extra. Our main objetive will be to analyze how the "father of pessimism" evidences rules for a possible eudemonology: that of living less unhappy.